Digital platform (Application Processing Interface or API) for interaction with, and data capture from, smallholder dairy cattle farmers - CGIAR Research Program on Livestock (2019)
Digital tools for data capture on dairy cattle performance on smallholder farms have been developed and used for longitudinal data capture in Tanzania, Ethiopia and Kenya, with collated data available for 59,963 dairy animals. The website (which requires users to register) is here: https://www.adgg.ilri.org/